Tourism And Erik Cohen In Thailand: Comparisons, Impacts, Mobilities And Encounters - King, Victor T. (Penerbit Universiti Sains Malaysia (USM Press), 2018)
The leading scholar in research in the feld of tourism in Thailand is Professor Erik Cohen. Not only has he contributed to the store of empirical material on Thailand on a wide range of tourism-related subjects, but he has been involved in an important series of debates about theories and paradigms in the sociologicalanthropological study of tourism. These debates examine the appropriate concepts to be deployed in understanding leisure activities and the transformations which tourism has set in motion. In tourism studies, there are several key ideas which have preoccupied researchers, many of them in relation to Thailand, to do with cultural “touristifcation” and commodifcation; imaging and representation; staging and authenticity; identity and ethnicity; host-guest relations; mediation and tour guides; trajectories of change; sequential typologies; and the tourist gaze. A most recent set of discussions generated by Erik Cohen and Scott Cohen has considered the utility of the sociological concept of mobilities and the problem of Eurocentrism in understanding local-level touristic encounters. The paper will critically review these concepts and provide contextual material on the development of tourism in Thailand during the past four decades. Until recently tourism in Thailand has tended to focus on selected sites along an axis which includes the northern hill or “tribal” regions, Chiang Mai and its environs, the greater Bangkok metropolitan area, and several beach and island resorts in southern Thailand, subjects which Erik Cohen has examined in considerable detail.